Clinical neurology and neuroanatomy : a localization-based approach - Berkowitz, Aaron, 1978- ([New York] : McGraw-Hill Education, 2022)
"[This book] offers a concise overview of fundamental neuroanatomy and the clinical localization principles necessary to diagnose and treat patients with neurologic diseases and disorders. Unlike other neurology textbooks that either focus on neuroanatomy or clinical neurology, Clinical Neurology and Neuroanatomy integrates the two in manner which simulates the way neurologists learn, teach, and think. Clinical Neurology and Neuroanatomy is divided into two main sections. In Part 1, clinically relevant neuroanatomy is presented in clinical context in order to provide a framework for neurologic localization and differential diagnosis. The diseases mentioned in localization-based discussions of differential diagnosis in Part 1 are then discussed in clinical detail with respect to their diagnosis and management in Part 2. Part 1 can therefore be consulted for a neuroanatomical localization-based approach to symptom evaluation, and Part 2 for the clinical features, diagnosis, and management of neurologic diseases." -- from website publisher
Part I: Neuroanatomy and neuroanatomic localization --- Ch. 1: Diagnostic reasoning in neurology and the neurologic history and examination -- Ch. 2: Introduction to neuroimaging and cerebrospinal fluid analysis -- Ch. 3: Overview of the anatomy of the nervous system -- Ch. 4: The motor and somatosensory pathways and approach to weakness and sensory loss -- Ch. 5: The spinal cord and approach to myelopathy -- Ch. 6: The visual pathway and approach to visual loss -- Ch. 7: The cerebral hemispheres and vascular syndromes -- Ch. 8: The cerebellum and approach to ataxia -- Ch. 9: The brainstem and cranial nerves -- Ch. 10: Pupillary control and approach to anisocoria cranial nerves 2 and 3 -- Ch. 11: Extraocular movements and approach to diplopia: cranial nerves 3, 4, and 6 -- Ch. 12: The Auditory and vestibular pathways and approach to hearing loss and dizziness/vertigo: cranial nerve 8 -- Ch. 13: Facial sensation and movement and approach to facial sensory and motor deficits: cranial nerves 5 and 7 -- Ch. 14: Cranial nerves 1, 9, 10, 11, and 12 -- Ch. 15: The peripheral nervous system and introduction to electromyography/nerve conduction studies -- Ch. 16: Radiculopathy, plexopathy, and mononeuropathies of the upper extremity -- Ch. 17: Radiculopathy, plexopathy, and mononeuropathies of the lower extremity --- Part II: Diseases of the nervous system --- Ch. 18: Seizures and epilepsy -- Ch. 19: Vascular Diseases of the Brain and Spinal Cord -- Ch. 20: Infectious Diseases of the Nervous System -- Ch. 21: Demyelinating diseases of the central nervous system -- Ch. 22: Delirium, dementia, and rapidly progressive dementia -- Ch. 23: Movement disorders -- Ch. 24: Neoplastic and paraneoplastic disorders of the nervous system and neurologic complications of chemotherapy and radiation therapy -- Ch. 25: Disorders of intracranial pressure -- Ch. 26: Headache -- Ch. 27: Peripheral neuropathy -- Ch. 28: Motor neuron disease -- Ch. 29: Disorders of the neuromuscular junction -- Ch. 30: Diseases of muscle -- Ch. 31: Leukodystrophies and mitochondrial disorders
Includes bibliographical references
Keywords: Neuroanatomy.http://id.loc.gov/authorities/subjects/sh85091113; Neurology.http://id.loc.gov/authorities/subjects/sh85091139; Nervous System -- anatomy & histology.(DNLM)D009420Q000033.https://id.nlm.nih.gov/mesh/D009420Q000033; Nervous System Diseases -- diagnosis.(DNLM)D009422Q000175.https://id.nlm.nih.gov/mesh/D009422Q000175; Neuroanatomy.(DNLM)D009445.https://id.nlm.nih.gov/mesh/D009445; Neurology.(DNLM)D009462.https://id.nlm.nih.gov/mesh/D009462